Pengaruh Media Interaktif Wordwall Terhadap Peningkatan Kemampuan Short-term memory Pada Anak Usia 5-6 Tahun : Indonesian - Fadila, Adinda Salma; Rusdiyani, Isti; Fatimah, Atin (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aimed to examine the effect of the interactive media Wordwall on improving short-term memory in children aged 5–6 years at TK Negeri Pembina, Kecamatan Cipocok Jaya, Serang, Banten. A quasi-experimental method with a nonequivalent control group design was employed. The study involved a sample of 30 children, divided into an experimental group (15 children) and a control group (15 children). The results revealed a significant improvement in short-term memory among children in the experimental group compared to the control group. The experimental group's average score increased from 42.6 (pretest) to 45.4 (posttest). Statistical analysis using SPSS Statistics 22 with a paired sample t-test showed a significance value of 0.000 (p < 0.05), indicating that the use of Wordwall had a significant effect on enhancing children's short-term memory. Additionally, children in the experimental group responded positively to the use of Wordwall, as evidenced by their active participation and ease in recalling information. These findings suggest that Wordwall is effective as an interactive learning medium to support the development of short-term memory in early childhood.